Biology and Morphometrics of Fall armyworm (Spodoptera frugiperda) in Chitwan, Nepal - Neupane, Shishir; Pokhrel, Suroj; Tiwari, Sundar; Bhandari, Ghanashyam; Adhikari, Pratibha; Poudel, Sudeep (International Journal of Applied Biology, 2023)
The Fall armyworm (FAW) Spodoptera frugiperda, native to the Americas, is an important invasive and polyphagous pest threatening cereal production. Abiotic and biotic factors, including climatic uncertainty and insect pests like S. frugiperda, pose threats. Detected in East Africa in 2016 and reported in Nawalpur, Nepal, on May 9, 2019, FAW has led to a 34% decline in maize yields. Studying FAW's biology and morphometrics is crucial for understanding its habitat and ecology, essential prerequisites for adopting integrated management strategies. Biological parameters such as incubation period, larval and pupal duration, pre-oviposition and, oviposition periods, male and female adult longevity, larval and pupal mortality, sex ratio (male: female), and morphometrics of egg, larvae, pupa, and adult were measured. The incubation period (2-3 days), larval and pupal periods (13-18 and 9-12 days) with overall life duration (31-45 days) were recorded in maize. Head capsule width of the first, second, third, fourth, fifth, and sixth instar were recorded as 0.52±0.05, 0.73±0.05, 1.1±0.05, 1.74±0.12, 2.04±0.15, and 2.91±0.23 mm respectively. Mean body length of different larval instars were recorded as 3.33±0.26, 6.92±1.07, 13.11±1.45, 16.82±1.57, 28.68±1.75, and 34.56±1.99 mm for the first, second, third, fourth, fifth, and sixth instar respectively.